Attenuation of neuroinflammation and Alzheimer's disease pathology by liver x receptors - Zelcer, Noam; Khanlou, Negar; Clare, Ryan; Jiang, Qingguang; Reed-Geaghan, Erin G; Landreth, Gary E; Vinters, Harry V; Tontonoz, Peter (Proceedings of the National Academy of Sciences - PNAS, 2007)
Alzheimer's disease (AD) is an age-dependent neurodegenerative disease that causes progressive cognitive impairment. The initiation and progression of AD has been linked to cholesterol metabolism and inflammation, processes that can be modulated by liver x receptors (LXRs). We show here that endogenous LXR signaling impacts the development of AD-related pathology. Genetic loss of either Lxralpha or Lxrbeta in APP/PS1 transgenic mice results in increased amyloid plaque load. LXRs regulate basal and inducible expression of key cholesterol homeostatic genes in the brain and act as potent inhibitors of inflammatory gene expression. Ligand activation of LXRs attenuates the inflammatory response of primary mixed glial cultures to fibrillar amyloid beta peptide (fAbeta) in a receptor-dependent manner. Furthermore, LXRs promote the capacity of microglia to maintain fAbeta-stimulated phagocytosis in the setting of inflammation. These results identify endogenous LXR signaling as an important determinant of AD pathogenesis in mice. We propose that LXRs may be tractable targets for the treatment of AD due to their ability to modulate both lipid metabolic and inflammatory gene expression in the brain.